Proceedings of the International Conference on Psychological Studies (ICPSYCHE 2020) 2021
DOI: 10.2991/assehr.k.210423.042
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Family in Introducing Early Sexual Education to Children

Abstract: Sexual education in Indonesia is remained Taboo, so many parents and schools do not have the awareness to provide sexual education to the children. However, some families tried to educate their children about sexuality. This study answers questions raised which how parents are involved in providing sexual education to early childhood. Researchers used a qualitative approach. Depth interviews have been done to the five parents. Researchers found three main themes which are relationships between parents and chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Families have responsibility and awareness in understanding children's sexual development without being queried by their children beforehand (Güder & Alabay, 2018). In a study conducted by Rakhmawati et al (2021), it was found that parents as respondents have different perspectives in terms of the children's age level to prepare for sexuality education. Open-minded parents perceived and realized that the understanding related to sexuality education should be explicitly conveyed according to the appropriate age level.…”
Section: Role Of Parentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Families have responsibility and awareness in understanding children's sexual development without being queried by their children beforehand (Güder & Alabay, 2018). In a study conducted by Rakhmawati et al (2021), it was found that parents as respondents have different perspectives in terms of the children's age level to prepare for sexuality education. Open-minded parents perceived and realized that the understanding related to sexuality education should be explicitly conveyed according to the appropriate age level.…”
Section: Role Of Parentsmentioning
confidence: 99%
“…Matters associated with their body, organ functions and also the differences in their body parts are among the topics that are often queried by children. Therefore, two-way communication between parents and children is vital for sexuality education, and open discussion about sexuality-related problems is also demanded (Rakhmawati et al, 2021). In addition, parents should monitor children's activities, control the use of gadgets and know their children's friends to prevent misleading information related to sexuality (Walsh & Brandon, 2011).…”
Section: Role Of Parentsmentioning
confidence: 99%
“…CSA occurs because of the accessibility of violent perpetrators, strangers, or the closest person to the children who become victims, that can be occurred in institutions, schools, and homes (Briggs, 2014;Lozano et al, 2012;Rakhmawati et al, 2021). CSA is an act that involves sexual activities, both on purpose or accidentally, which most of the victims are children because they cannot refuse or give consent to the perpetrators (Sumera, 2013;Waid-Lindberg & Mohr, 2019;Zhang et al, 2015).…”
Section: Jecce (Journal Of Early Childhood Care and Education)mentioning
confidence: 99%
“…Parents applied various strategies and learning methods in providing sexual education (Rakhmawati et al, 2021). Rakhmawati et al (Rakhmawati et al, 2021) mentioned that providing a consistent and appropriate education as a learning strategy could be used to provide sexual education.…”
Section: Jecce (Journal Of Early Childhood Care and Education)mentioning
confidence: 99%
See 1 more Smart Citation